EXAMINING THE ECONOMIC IMPACT OF CORRUPTION: ARE DIFFERENCES BETWEEN THE CLEANEST AND MOST CORRUPT COUNTRIES BEFORE AND DURING COVID-19? - Lestari Agusalim; Muhammad Ilham Alfiansyah; Puguh Prasetyoputra; Riko Noviantoro (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
The relevance of this study stems from the need to understand the impact of corruption on economic growth across various groups of countries, particularly before and during the COVID-19 pandemic. This study aims to analyze whether there are differences in the impact of corruption on economic growth between countries with the lowest and highest levels of corruption, both before and during the pandemic. Using panel data regression analysis with a fixed-effects model from 2012 to 2020 and covering 159 countries, the study supports the